A Rapid Spectrophotometric Determination of Thorium with DBCArsenazo as a Chromogenic Reagent - Zhai, Qing-Zhou; Zhang, Xiao-Xia; Chen, Liang (Asian Journal of Chemistry, 2010)
A simple, rapid and sensitive spectrophotometric method for the determination of trace amount of thorium(IV) has been developed using DBC-arsenazo (DBC-ASA) as a chromogenic reagent in a 1.0 mol L-1 hydrochloric acid solution. Absorbance was measured in 1 cm cell and the complex has the maximum peak of absorption at 622 nm. The complex of thorium thus formed, is stable for 1 h with constant absorbance. Beer's law is obeyed in the range 0-0.60 μg mL-1 of thorium concentration with an apparent molar absorptivity at ε622 nm = 7.15 × 104 L mol-1 cm-1 at 25 ºC. The linear regression equation of the method is A = 0.032C-0.004 [C: μg Th(IV)/ 10 mL], the correlation coefficient γ = 0.9991. The stoichiometric composition of the Th-(DBC-ASA) complex is 1:2. A large excess of cations and anions do not interfere with the determination of thorium. The proposed method was directly applied to the determination of thorium in hairtail and dried shrimps samples with satisfactory results. The relative standard deviation of nine replicate determinations and the recovery were over the range of 1.45-2.95 and 99.3-101.1 %, respectively.